A global synthesis of patterns in soil organic matter and temperature sensitivity along the altitudinal gradient - Li, Chao; Xiao, Chunwang; Li, Mingxu; Xu, Li; He, Nianpeng (Frontiers in Environmental Science, 2022)
Although it is important to determine how the global carbon (C) cycle is responding to climate change in our three-dimensional earth, variation in the soil organic matter (SOM) and temperature sensitivity (Q10) along the altitudinal gradient remain unclear globally. This study explored spatial variability in SOM and Q10 and its regulatory mechanisms from a three-dimensional perspective. We collected SOM and Q10 datasets from published studies for 010 cm soil depth along elevational gradients of mountain ranges globally. We found that SOM content in most mountains changed significantly with increasing altitude; unexpectedly, these changes with altitude significantly differed across different climate zones. Specifically, SOM content increased with increasing altitude in tropical and subtropical regions, while it decreased with increasing altitude in temperate and plateau regions. Climate factors (mean annual temperature and mean annual precipitation) and soil properties (total N content, C/N ratio, and pH) together accounted for 83% of spatial variation in SOM with altitude. Q10 values, under both laboratory incubation and in-situ studies, did not significantly correlate with altitude, and no apparent global patterns were detected (mean: 2.07); however, Q10 was regulated by variation in soil substrate quality along altitudinal gradients, to some extent. In the context of global climate change, this new information on SOM and Q10 in relation to altitude at a global scale might enhance our understanding of soil Cclimate feedbacks.